ICP-MS Measurement of 11B/10B Isotope Ratios in Grapevine Leaves and the Investigation of Possible Boron Isotope Fractionation in Grapevine Plants - Coetzee, P.P.; L., Greeff; Vanhaecke, F. (South African Journal of Enology and Viticulture, 2016)
The correlation between the 11B/10B ratio in grapevine leaves and that in the growth medium was established in a series of hydroponic experiments with grapevine cuttings for different cultivar/rootstocks combinations. The hydroponic growth medium was alternately spiked with boric acid containing B with natural isotope composition and B enriched in 10B, so as to vary the 11B/10B ratio. B isotope ratios in grapevine leaves were determined by quadrupole-based ICP-MS after digestion and complete matrix removal through microwave digestion and isolation of matrix-free B species using ion exchange separation. It was found that the B isotope ratios in the leaves were not identical to those in the growth medium, but that a change in the ratio in the growth medium induced a similar change in the leaves. For a particular cultivar/rootstock combination, a characteristic B isotope ratio was found that was different from the ratio in a group of plants with a different cultivar/rootstock combination.